Factor analysis of the self-report version of the strengths and difficulties questionnaire in a sample of children with intellectual disability. - Haynes, A.; Gilmore, L.; Shochet, I.; Campbell, M.; Roberts, Clare (Pergamon, 2013)
The rate of emotional and behavioural disturbance in children with intellectual disability (ID) is up to four times higher than that of their typically developing peers. It is important to identify these difficulties in children with ID as early as possible to prevent the chronic co-morbidity of ID and psychopathology. Children with ID have traditionally been assessed via proxy reporting, but appropriate and psychometrically rigorous instruments are needed so that children can report on their own emotions and behaviours. In this study, the factor structure of the self-report version of the Strengths and Difficulties Questionnaire (SDQ) was examined in a population of 128 children with ID (mean age = 12 years). Exploratory and Confirmatory Factor Analysis showed a three factor model (comprising Positive Relationships, Negative Behaviour and Emotional Competence) to be a better measure than the original five factor SDQ model in this population.